Кварцеве скло в металургії сталі - Немсадзе, Г.Г.; Тонкушин, А.Ф. (Physico-technological Institute of Metals and Alloys, 2023)
The article is devoted to quartz glass, its types and main differences. The article describes opaque quartz glass, because this type has found application in metallurgy. Three basic definitions are disclosed: quartz, glass and smelting. The main attention is devoted to the production of quartz glass (fused quartz) by plasma melting. The main property of fused silica mainly lies in its high thermal stability, due to the structure of the supercooled liquid. Special refractory products used in metallurgy to protect a metal stream from secondary oxidation, including refractories based on fused silica in comparison with corundum graphite are described. The main problem of the use of refractory products based on fused silica is highlighted, namely, low resistance when casting manganese steels. Photos of products before and after usage when casting steel at the continuous casting machine (CCM) are given. The process of wear of fused silica refractory in liquid steel is presented as an electrochemical process of the interaction of quartz oxide and manganese ions at high temperatures. Attention is drawn to the fact that the electrochemical process of obtaining a chemically uniform refractory occurs according to a simple chemical formula with the formation of manganese oxide and the transition of silicon into molten steel. In this case, the formation of complex chemical compounds that can crystallize in steel in the form of non-metallic inclusions does not occur, as occurs when corundumgraphite refractories are complex in composition. It is concluded that the process of interaction of refractories based on fused silica with a molten steel should be considered as an electrochemical process between silicon oxide and free manganese, while the effect of alloying and other components of steel, including iron, on the wear of the refractory is much weaker.